Estudo da atividade das espécies amazônicas: Pradosia huberi Ducke. e Attalea excelsa Mart. sobre o sistema cardiovascular em ratos - Medeiros, Alessandra Azevedo Nascimento de (2008)
The pharmacological effects of Pradosia huberi (EHP) and Attalea excelsa (EAE) ethanolics extracts on the cardiovascular system were studied in rats using a combined in vivo and in vitro approach. In non-anaesthetized rats, EPH (5, 10 or 20 mg.Kg-1 i.v.) injections produced hypotension (-5.6±0.5; -8.8±1.3 and -32.6±6.6%, respectively) and bradicardia (-0.30.9; - 4.42.2 and -45.36.0%, respectively) (n=6). After acute treatment with a muscarinic agonist (atropine, 2 mg.Kg-1, hypotension (-5.0 ± 0.8, -6.4 ± 0.9 and -11.6 ± 1.8%, respectively ) and bradicardia (-1.2 ± 0.4, -2.9 ± 0.8 and -8.1 ± 2.2%) were significantly attenuated. Hexamethonium, a ganglionic blocker, also attenuated the effect of EPH. After L-NAME both answers were not modified. In isolated rat mesenteric artery rings, with intact endothelium, EPH (1, 3, 10, 30 and 100g/mL) induced concentration-dependent relaxation of the contractions induced by Phe (10 M) (EC50=17.14±2.9; Emax=87.8±2.9, n=8) and this effect was abolished by removal of vascular endothelium, suggesting the involvement of a mechanism endothelium-dependent. Fractions and 2-3dihydromyricetin-3-O--L-rhamnoside isolated from EPH did not relax or relaxed with less potency and effectiveness the preparation pre-contracted with Phe. The concentration-response curve for EPH was significantly shifted to the right with L-NAME (100 M), ODQ (1M), KCl 20mM, indomethacin (1M) + L-NAME (100M), 4-AP (1mM), BaCl2 (30 μM), TEA (1mM). In the presence of L-NAME (100M) + L-arginine (1mM) EHP relaxed preparations without changing the Emax. EPH did not induce relaxation on KCl 80 mM precontracted rings. Once in the presence of atropine (1M), indomethacin (1M), glibenclamide (10M) and apamin (1μM) the curve of EPH was not altered. We concluded that the hypotensive effect of EPH seems result of its vasorelaxant action and can involve an indirect activation of muscarinic heart receptors and still that the vascular effect of EPH can involve the activation of the eNOS-NO-GMPc ways well as the participation of BKCa, KV, and Kir potassium channels in vascular smooth muscle. EAE (5, 10, 20, 40 and 60 mg/kg i.v.) induced hypotension (- 3.7±1.2; -6.1±2.3; -8.5±1.3; -9.9±1.6 and -11.2±1.8%, respectively) and tachycardia (3.8±1.7; 4.0±1.6; 3.8±2.0; 3.7±3.1 and 12.4±2.7%, respectively) (n=5) probably due to a reflex response. In isolated rat mesenteric artery rings, EAE (1, 3, 10, 30, 100, 300, 500 and 1000 g/mL)induced relaxation in a concentration-dependent manner in both intact-(EC50 = 172.3 ± 36.9, Emax = 100 ± 0.0%) or removed-endothelium rings (EC50 = 166,7±31,4, Emáx = 92,2±7,1%) pre-contracted with Phe 10M with the same potency and effectiveness (n=6). These results suggest that EAE acts by an endothelium-independent mechanism. Subsequent experiments were accomplished in preparations without endothelium. In preparation pre-incubated with KCl 20 mM, the vasorelaxant activity of EAE was not changed (EC50 = 108.1 ± 10.7 and Emáx = 95.9 ± 4.4%). EAE relaxed with the same potency rings precontracted with KCl 80 mM (Emax = 97.1 ± 1.5%) or with Phe (Emax = 92.2 ± 7.1%) suggesting that EAE acts on the voltage-dependent Ca2+-channels. Furthermore, in depolarizing medium nominally without Ca2+, EAE antagonized CaCl2-induced contractions in a concentrationdependent manner. EAE (1, 3, 10, 30, 100, 300, 500 and 1000 g/mL) induced relaxation concentration-dependent, contractions elicited by the L-type Ca2+ channel agonist, S(-)-Bay K 8644 (Emáx = 128.8±5.8%, n=8). EAE did not alter transient contractions induced by caffeine (20 mM) and little influenced those induced by Phe (10 M). In rat isolated atrium, EAE produced negative inotropic and cronotropic effect. Electrophysiological studies on cells A7r5 (100 M) EAE inhibited Ba2+ current through the CaVL1.2. In conclusion, the results suggested that the hypotensive effect of EAE is due to its vasorelaxant action that seems to be attributed to the influx of Ca2+ through CaV 1.2 channels in vascular myocytes.